Tissue distribution and trophic magnification of trace elements in typical marine mammals in Bohai and north Yellow Seas. (November 2022) - Tian, Jiashen; Lu, Zhichuang; Sanganyado, Edmond; Gan, Zhiwei; Wang, Zhen; Kong, Zhongren; Wu, Jinhao; Liu, Wenhua
Abstract: A total of 20 stranded spotted seals ( Phoca largha ) and 9 stranded minke whales ( Balaenoptera acutorostrata ) were collected from Liaodong Bay and the northern part of the Yellow Sea to investigate the tissue distribution (liver, kidney, heart, lung, and muscle), risk, and trophic magnification of 13 trace elements (TEs, Hg, As, Cd, Co, Cr, Cu, Mn, Ni, Pb, Se, Sn, V, Zn). The 13 TEs were all detected in all spotted seal and minke whale tissue samples, with mean concentrations ranging from 0.041 to 136.3 mg kg −1 dry weight (dw) and 0.022 to 152.6 mg kg −1 dw, respectively. Zn was the dominant contaminant in all tissues for both spotted seals and minke whales. There was tissue-specific distribution of TEs in both marine mammals, and the TEs tended to accumulate in internal organs. Significant positive correlations were found in the body length of the spotted seals and minke whales among some of the TEs, especially for Cd in the internal organs. Gender-dependent distribution of the TEs was not obtained for the spotted seal. Ecological risk evaluation for spotted seals and minke whales suggested that greater concern should be given to Hg, As, and Se. Based on the TE concentrations detected in this study and trophic levels determined by stable carbon and nitrogen isotopes, trophic level-associated biodilution was obtained for As, Cd, Co, Cu, Mn, Pb, Se, Sn, and V in the spotted seal, while Zn displayed a significant biomagnification trend with increasing trophic levels. In the case of the minke whale, As, Cd, Co, Mn, Pb, Se, and V displayed significant biomagnification trends with increasing trophic levels. Graphical abstract: Unlabelled Image Highlights: Trace elements (TEs) were detected in all spotted seal and minke whale tissues. Zn concentrations were the highest in both marine mammals. The TE concentrations had significant positive correlation with body lengths. Trophic biodilution of As, Cd, Co, Cu, Mn, Pb, Se, Sn, and V occurred in spotted seal. Trophic biomagnification of As, Cd, Co, Mn, Pb, Se, and V occurred in minke whale.